EKSPLORASI HAMBATAN DALAM PENERAPAN SISTEM AKUNTANSI SEDERHANA PADA UMKM DI KOTA SERANG - Kartika, Rika; Amyati, Amyati; Sari, Diah Permata (Yayasan Education and Social Center, 2025)
This study aims to explore the barriers faced by MSMEs (Micro, Small, and Medium Enterprises) in Serang City in implementing a simple accounting system. The research found that the main obstacles include limited human resources, insufficient capital, low technology acceptance, and time constraints. These factors hinder MSMEs from adopting structured and efficient accounting practices. Limited knowledge in accounting, especially in managing finances, was a significant challenge, along with the lack of access to advanced accounting tools due to financial constraints. Additionally, MSME owners often resist using accounting technology, perceiving it as complex and unnecessary for their business needs. Time limitations were also identified, as many MSME owners prioritize daily operations over financial record-keeping. To overcome these barriers, the study recommends comprehensive support, such as intensive training and assistance for MSME owners, along with providing affordable access to accounting technologies.